2013
DOI: 10.1021/ci400195v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Characterizes Substrate-Binding Sites and Efflux Modulation Mechanisms within P-Glycoprotein.

Abstract: P-Glycoprotein (Pgp) is one of the best characterized ABC transporters, often involved in the multidrug-resistance phenotype overexpressed by several cancer cell lines. Experimental studies contributed to important knowledge concerning substrate polyspecificity, efflux mechanism, and drug-binding sites. This information is, however, scattered through different perspectives, not existing a unifying model for the knowledge available for this transporter. Using a previously refined structure of murine Pgp, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 101 publications
13
172
3
1
Order By: Relevance
“…The recent docking study, however, proposed that the verapamil binding site was different from "R" site, not only from "H" site. 32 The result of this docking study is controversial comparing to our result of docking study that verapamil binding site is similar to "R" site. Verapamil was known as the ligand which preferentially binds to "H" site in 1990's.…”
mentioning
confidence: 61%
“…The recent docking study, however, proposed that the verapamil binding site was different from "R" site, not only from "H" site. 32 The result of this docking study is controversial comparing to our result of docking study that verapamil binding site is similar to "R" site. Verapamil was known as the ligand which preferentially binds to "H" site in 1990's.…”
mentioning
confidence: 61%
“…Structure-based approaches which are also called protein-based studies are the most useful methods when the structure of the receptor, usually a protein, is available. They deal with modeling the ligand-receptor interactions through docking (Vitale et al, 2013;Ferreira et al, 2013;Shahlaei et al, 2013) and a more accurate method, molecular dynamics (MD) simulation (Hucke et al, 2014;Chavan et al, 2011;Shahlaei et al, 2011). Such studies provide information on possible types of interaction forces between the ligand and its receptor and also information on the nature of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses had shown that docking studies performed by various approaches are reliable strategies to identify compounds that interact directly with ABCB1 [51][52][53]. From our previous studies, the docking scores obtained for a group of 54 substrates (including well-known substrates such as ivermectin and cyclosporine) had an average docking score of ≤ −12, like those we observed for enzastaurin in the 3G60 structure, while a group of 69 nonsubstrates had an average score of ~ −10 kcal/mol using MOE software and the same docking methodology [54,55].…”
Section: Discussionmentioning
confidence: 99%